THE EFFECTIVENESS OF CREATIVE PROBLEM SOLVING ON LOGICAL THINKING ABILITY AND MASTERY OF CONCEPTS - Dina Shafira; dewi lengkana; Tri jalmo; Dina maulina (JURNAL PENA SAINS, 2020)
This research aims to determine the effect of Creative Problem Solving (CPS) on logical thinking ability and concept achievement. The design was a nonequivalent pretest-posttest control group design. The samples were 60 students of X MIA 1 and X MIA 3 selected through cluster random sampling technique. Data on logical thinking ability obtained using the Test of Logical Thinking (TOLT and data on concept achievement (cognitive aspects) gathered using pretest and posttest. Both data were analyzed by Independent Sample t-Test at a 5% confidence level. The results showed that CPS give effect significantly the experimental class logical thinking ability (0.41± 0.13) was higher than the control class (0.21 ± 0.07). The mastery of concepts on the experiment class (0.61 ± 0.20) higher than the control class (0.41 ± 0.20). It means that CPS influences students’ logical thinking ability and mastery of concepts.